Organoleptic Quality of Goat’s Milk Ice Cream with the Addition of Moringa Leaf Flour (Moringa oleifera) - Suhendri; N Ginting; Nurjama’yah br Ketaren; Ibrahim N S (Jurnal Peternakan Integratif, 2024)
The utilisation of goat's milk and moringa leaves as processed ice cream food products is one alternative that can be done by goat milk farmer community. This study aims to determine the effect of the addition of moringa leaf flour (Moringa oleifera) on the organoleptic quality of ice cream.  The research was conducted at the Production Laboratory of the Universitas Sumatera Utara in September-October 2023. The study used a completely randomised design (CRD) with 4 treatments and 3 replication where P0 without the addition of moringa flour, P1 = 20 grams of moringa flour, P2 = 25 grams of moringa flour, P3 = 30 grams of moringa flour. The parameters observed were organoleptic tests, namely colour, aroma, texture, taste and liking. The results showed that the addition of moringa flour (Moringa oleifera) with the treatment of 20 grams to the making of goat milk ice cream was liked by panelists in terms of colour, aroma, texture, taste and liking compared to the treatment of 25 grams and 30 grams.  In conslusion that ice cream with goat's milk added with 20% moringa leaf flour has preferable organoleptic quality.